Manajemen Komunikasi Pelayanan dalam Mengatasi Keluhan Pelanggan di Asimetri Kopi Kabupaten Bogor - H Halimatusha’diah; Meryana Chandri Kustanti; Dian Sari (LPPM STIKOM Tunas Bangsa, 2022)
Coffee Asymmetry is a coffee shop that wants to provide excellent service to its customers. Excellent service is considered very important to build customer comfort and loyalty. The partner's problem is that there are no guidelines for dealing with customer complaints based on communication management, therefore one of the efforts that needs to be done is to maximize communication skills in improving excellent service so that customers remain satisfied and comfortable. In realizing this goal, it is necessary to provide training to Coffee Asymmetry staff in improving communication skills. The debriefing was carried out by Lecturers of Informatics Engineering at Indraprasta PGRI University through the LPPM at Indraprasta PGRI University in the Community Service program. The debriefing is done offline at Coffee Asymmetry. The method of implementing this activity is material delivery, practical assistance, and discussion/question-and-answer. Based on further observations, the results obtained from this activity revealed that 1) all participants were able to understand how to provide excellent service and were able to communicate confidently; 2) all enthusiastic participants will try to practice communication management materials in dealing with customer complaints; 3) almost all participants looked confident when dealing with customers; 4) participants can clearly understand the importance of self-confidence in dealing with customer complaints; and 5) almost all participants already understand how to communicate properly when dealing with customer complaints, although they must continue to practice so that they are more flexible and not rigid.